THE TRANSLATION SHIFT ANALYSIS OF NOMINAL GROUPS IN THE MARTIAN MOVIE SUBTITLE - Meidha, Mia Putri (2017)
This research aims to analyze the translation shifts of nominal groups that occur in The Martian movie subtitle, and investigates how the translation shifts affect meanings. This study employs a qualitative descriptive method as proposed by Cresswell (2007). The data of this study are taken from the movie transcriptions and subtitle in The Martian (2015) movie. The data are analyzed by using Gerot and Wignell's (1994) theory of nominal groups and Catford's (1965) category of translation shifts which include structure shift, class shift, unit shift, and intra-system shift. The analysis shows that the process of translating involves single and double translation shifts. In single translation shift, structure shift is the most dominant translation shift (75,7%). In double translation shift, the most dominant shift is the combination of structure and intra-system shift (12,6%). The analysis also shows that the translation process involves the combination of unit and intra-system shift (0,8%), and the combination of class and unit shift (0,3%). The translation shifts are found affecting meanings. There are 37 nominal groups which experience changes in meanings due to the translation shift strategy. The implication of the study relates to the significance of understanding linguistic features as a choice to convey certain meanings in another language.;--- Penelitian ini bertujuan untuk menganalisis pergeseran terjemahan (translation shift) frasa nominal dalam subtitle film The Martian, serta menyelidiki bagaimana pergeseran terjemahan tersebut mempengaruhi makna. Penelitian ini menggunakan metode deskriptif kualitatif yang diusulkan oleh Cresswell (2007). Data penelitian ini diambil dari transkrip dan subtitle film The Martian (2015). Data penelitian dianalisis dengan menggunakan teori Gerot and Wignell (1994) tentang frasa nominal dan teori Catford (1965) tentang kategori pergeseran terjemahan yang meliputi structure shift, class shift, unit shift, and intra-system shift. Analisis data menunjukkan bahwa proses penerjemahan meliputi pergeseran terjemahan tunggal dan ganda. Dalam pergeseran terjemahan tunggal, structure shift merupakan kategori pergeseran terjemahan yang paling dominan (75,7%). Dalam pergeseran terjemahan ganda, kategori yang paling dominan adalah gabungan antara structure dan intra-system shift (12,6%). Analisis data juga menunjukkan bahwa proses penerjemahan meliputi gabugan antara unit dan intra-system shift (0,8%), dan gabungan antara class dan unit shift (0,3%). Pergeseran terjemahan dapat mempengaruhi makna. Terdapat 37 frasa nominal yang mengalami pergeseran makna karena strategi penerjemahan. Implikasi dari penelitian ini berkaitan dengan pentingnya memahami fitur-fitur linguistik sebagai pilihan untuk menyampaikan makna tertentu dalam bahasa lain.